A pilot study of a Scripture-based trauma healing model for adults in Nicaragua - Schultz, Tammy (Mental health, religion & culture, 2016)
With the rising attention to global trauma, there is increased interest in utilising effective trauma healing (TH) models, especially those that integrate a spiritual component. This paper examines the effectiveness of a Scripture-based TH model developed by the Trauma Healing Institute utilised in a pilot study with Nicaraguan adults who experienced non-sexualised-related crime, disaster-related trauma, and/or interpersonal violence. An additional focus of this study was on whether increased spiritual well-being would result from this healing model. In this first empirical study on the TH model, initial results indicated that participants (N = 23) experienced both a reduction in trauma-related symptoms as well as an upward trend in spiritual well-being from pre-test to six-month follow-up. Spearman results also showed an inverse relationship between trauma symptoms and spiritual well-being. Factors that may have impacted results, limitations to this pilot study, and considerations for future studies are discussed.